An update on the use of gamma (multi)sensory stimulation for Alzheimer’s disease treatment - Manippa, Valerio; Palmisano, Annalisa; Filardi, Marco; Vilella, Davide; Nitsche, Michael A.; Rivolta, Davide; Logroscino, Giancarlo (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is characterized by reduced fast brain oscillations in the gamma band (γ, > 30 Hz). Several animal studies show that inducing gamma oscillations through (multi)sensory stimulation at 40 Hz has the potential to impact AD-related cognitive decline and neuropathological processes, including amyloid plaques deposition, neurofibrillary tangles formation, and neuronal and synaptic loss. Therefore Gamma Entrainment Using Sensory stimulation (GENUS) is among the most promising approaches for AD patients’ treatment. This review summarizes the evidence on GENUS effectiveness, from animal models to AD patients. Despite the application on human is in its infancy, the available findings suggest its feasibility for the treatment of AD. We discuss such results in light of parameter improvement and possible underlying mechanisms. We finally emphasize the need for further research for its development as a disease-modifying non-pharmacological intervention.